PERKEMBANGAN PENGUMPULAN ZAKAT PADA BAZNAS KABUPATEN TANAH DATAR PERIODE 2010 s.d. 2014 - FAHLEFI, RIZAL (JURIS (Jurnal Ilmiah Syariah), 2016)
Collecting zakat (divine tax) is one of the main responsibilities of amil (the collector) of zakat. In fulfilling this kind of responsibility, BAZNAS of Tanah Datar Regency has done is successfully. This study, therefore, aimed figuring out the zakat collecting growth in BAZNAS of Tanah Datar Regency during 2010-2014 periods in terms of the nominal, source, and efforts made in collecting the zakat. To achive the goals, this study employed case study. The findings showed that the numbers of zakat collected during the period increased significantly with a total of more than IDR 34.44 billions. The increase was much far above the average that could be achieved nationally. In term of source of zakat, there was extended sources from profession zakat to other sources, such as trade and services zakat. In order to support its efforts to collect zakat successfully, BAZNAS of Tanah Datar Regency made continuous efforts to increase Zakat Collecting Unit (UPZ), established marketing team, distributed marketing tools, dan conducted massive zakat socialization